Somewhat Opinionated An American dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Peter Sharp Theatre at Juilliard, 2 October. Joyce Theatre, 5 October. Howard Gilman Opera House, Brooklyn Academy of Music, 11 October. Joyce Theatre, 18 October. New York City Center, 19 October-6 November. Howard Gilman Opera House, Brooklyn Academy of Music, 8 November. Rose Theatre, Lincoln Center, 9 November. Joyce Theatre, 10 November. Skirball, 11 November. New York State Theatre, 22 November. New York City Center, 30 November-1 January. The Duke on 42nd Street, 1 December. Howard Gilman Opera House, Brooklyn Academy of Music, 5 December. Joyce Theatre, 20 December. PALABRAS CLAVE: BalletTech company, Steve Reich, Eliot Feld, Stephen Mill's Ballet Austin, Zhang Yimou, National ballet of China, Parsons Dance Company, Mauro Bigonzetti, Garth Fagan, Anne Teresa De Keersmaeker, Lar Lubovitch dance Company, An American Music Celebration, Alvin Ailey American Dance Theater, Armitage Gone!, Sasha Waltz, Savion Glover.